Personer med demenssykdom i sykehjem: Refleksjon over livet - Drageset, Ingrid; Normann, Ketil; Elstad, Ingunn (Nordisk tidsskrift for helseforskning, 2013)
AbstractPersons with dementia disease in nursing homes: Reflection about lifeThe article is based on interviews with eight individuals with dementia disease living in nursing homes in Northern Norway. They were asked to tell about their lives, especially habits, interests and activities through the lifespan. Narrative analysis was conducted, phases and happenings through the lifespan were especially important for the interpretation. The persons reflected about their lives, they held up what had been meaningful to them, what they wanted to continue in the nursing home, and how they experienced living with dementia disease. The article holds up the importance of letting the patient tell from his or her life to be able to experience sense of coherence when moving to the nursing home. Continuing contact with family, relationship with nature, animals, local food traditions, singing and music, were also told about as meaningful activities throughout lifespan and in the nursing home.
Keywords: Nursing home; Dementia disease; lifespan; identity; continuity; Northern Norway; Sykehjem; demenssykdom; livsløp; identitet; kontinuitet; Nord-Norge